An extension of a discrete-module-beam-bending-based hydroelasticity method for a flexible structure with complex geometric features. (1st September 2018) - Zhang, Xiantao; Lu, Da
Abstract: The discrete-module-beam-bending based hydroelasticity method proposed by Lu et al. (2016) deals with the hydroelastic response of a flexible structure by discretising it into several rigid submodules which are connected by Euler-Bernoulli beam elements. A stiffness matrix is determined in terms of the geometrical and physical properties of the flexible structure for each beam element and it has an analytical form for simple geometric features such as a rectangular cross section unchanged along the longitudinal direction. However, the analytical stiffness matrix may not exist for a flexible structure with complex geometric features. In the present study, with the aid of finite element method, the discrete-module-beam-bending-based hydroelasticity method proposed by Lu et al. (2016) is extended to be applicable for a flexible structure with complex geometric features. Highlights: Integration of FEM into a discrete-module-beam-bending-based hydroelasticity method. The extended hydroelasticity method is applicable for flexible structures with complex geometric features. Validation of the extension is performed.